The effect of fuel injection at evevated temperature on the performance on a diesel engine - 400006 Yap, Tze Chuen (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2000